Efficacy of Intravitreal Bevacizumab with Cryotherapy for Zone II Stage 3 + Retinopathy of Prematurity - Kasiri, Ali (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: Vascular endothelial growth factor (VEGF), originally known as vascular permeability factor with different important roles in triggering vasculogenesis and angiogenesis. This protein has a pivotal role in retinopathy of prematurity (ROP). This study aims to evaluate the efficacy of VEGF inhibitor with cryotherapy for zone II Stage 3 plus ROP. Methods: In a prospective controlled clinical trial was performed on 6 infants, 12 eyes with zone II Stage 3 plus ROP. There was neurological visual impairment (NVI) in one eye. Under general anesthesia after confirmation of staging, prep and drape done cryotherapy of avascular retina in two rows combined with intravitreal injection of 0.625 mg bevacizumab in 0.025 ml was performed, and in one eye with iris neovascularization 0.625 mg intracameral bevacizumab injected too, all eyes were examined in 3 days, 1th, 4th, and 12th week after procedure. Results: Regression of NVI in 3 days and retinal neovascularization in 1 week period post operation. Conclusion: One session cryotherapy combined with intravitreal injection of 0.625 mg of bevacizumab can be effective in management of zone II Stage 3 plus ROP, more studies with more participants seems to be necessary.